1997
DOI: 10.1116/1.580921
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of acetone on the surfaces of the oxides of uranium

Abstract: The reactions of acetone were investigated on α U3O8 (stoichiometric and H2 reduced) by temperature programmed desorption. The surface and bulk characteristics of U oxides were investigated by x-ray photoelectron spectroscopy (XPS) and x-ray diffraction (XRD). The comparison between the XPS U 4f7/2 binding energy of β UO3, α U3O8, and UO2 indicated that the U cations in U3O8 are composed of +5/+6 (2/1) or +4/+6 (1/2) oxidation states. XPS of H2 reduced α U3O8 (at 800 K) indicated a shift of the U 4f7/2 binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
9
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 0 publications
6
9
1
Order By: Relevance
“…Although butene and propanol formation from acetone has been reported over various metal oxides [47][48][49], these species were not observed in this study during acetone TPD over reduced Co/ZrO 2 . This may be due to C-C cleavage activity of the Co-based catalysts.…”
Section: Acetonecontrasting
confidence: 77%
“…Although butene and propanol formation from acetone has been reported over various metal oxides [47][48][49], these species were not observed in this study during acetone TPD over reduced Co/ZrO 2 . This may be due to C-C cleavage activity of the Co-based catalysts.…”
Section: Acetonecontrasting
confidence: 77%
“…The localized 5f peak is similar in intensity and located in a similar position to the localized 5f peak observed upon oxidation of uranium above UO 2 [21], suggesting that following reaction with NO (>10 L exposure) uranium is in a higher oxidation state than +4 and there is increased 5f electron involvement in bonding. Broadening of the core-level spectra would support this observation and may suggest the possible presence of a combination of +3 (UN) [18], +4 (380.0 eV) and +6 (381.2 eV) oxidation states [22,23] within the sampling depth of XPS.…”
Section: Adsorption Of Nitric Oxidesupporting
confidence: 59%
“…This indicates that in the surface region the oxidation state of the uranium approaches U VI , as observed for UO 3 [26]. Since we would expect no localised U 5f feature in the UPS spectra for a U VI compound, the 5f peak observed at the highest exposures could be a result of an underlying lower oxide in agreement with the U 4f spectra, where the observed binding energy and peak broadening suggest a combination of +4 and +6 oxidation states [22,23]. …”
Section: Adsorption Of Nitrogen Dioxidesupporting
confidence: 51%
“…2. We have previously shown that U oxides are active for several C-C bond formation reactions: making isobutene from acetone on α-U 3 O 8 [18]; making furan from acetylene [19], ethylene [20], acetaldehyde [21], or ethanol [22] on β-UO 3 ; and making ethylene from formaldehyde on UO 2 (111) single crystals [23].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is considerable knowledge now of the bulk properties of this oxide system, our understanding of their surface reactions lags that of early transition metal oxides. Among the studies on uranium oxides conducted so far are organometallic investigations [1][2][3][4], theoretical calculations [5][6][7], surface spectroscopy [8,9], and catalytic studies [10][11][12][13][14][15][16][17][18]. Uranium oxides can be used as catalysts, promoters, or supports for other oxides and metals.…”
Section: Introductionmentioning
confidence: 99%